Self-determination in relation to quality of life in homeless young adults: Direct and indirect effects through psychological distress and social support. Issue 2 (4th March 2017) - Krabbenborg, Manon A.M.; Boersma, Sandra N.; van der Veld, William M.; Vollebergh, Wilma A.M.; Wolf, Judith R.L.M.
Abstract: The self-determination theory emphasizes the importance of satisfaction with autonomy, competence, and relatedness for a person's psychological growth and well-being. This study examines associations between autonomy, competence, and relatedness with quality of life in homeless young adults; and whether possible associations are mediated by psychological distress and perceived social support. By means of face-to-face interviews, 255 homeless young adults who receive care from 10 Dutch shelter facilities for homeless young adults have been interviewed ( M age = 20, 77% male, 51% Dutch Nationality) shortly after entering the facility. Autonomy, competence, and relatedness are all associated with quality of life, with competence as the highest correlate. Psychological distress mediates both competence and autonomy, and social support mediates competence as well as relatedness. These findings emphasize the importance of intervention programs for homeless young adults, focusing on the enhancement of self-determination, especially competence, to improve their quality of life.